Designing for kids :creating for playing, learning, and growing - Castella, Krystina (Routledge, 2019)
Designers, especially design students, rarely have access to children or their worlds when creating products, images, experiences and environments for them. Therefore, fine distinctions between age transitions and the day-to-day experiences of children are often overlooked.